Multifunctional polymer and polymer-hybrid nanoparticles for triggered drug release and potent combined photothermal-chemotherapy - Zhang, Yuanyuan (2016)
Various polymer based nanoparticles have been developed and explored as therapeutic nanovehicles for the treatment of cancer. In an effort to reduce the side effects and minimize the undesirable damage to normal tissues, the drug molecules could be incorporated into these nanocarriers by physical loading or covalent conjugation and successfully delivered into the tumor sites and cancer cells. However, traditional polymeric drug delivery system suffers the slow drug release inside tumor tissues or cancer cells, which might compromise its ultimate therapeutic effects. Thus, tremendous efforts have been put forward by the researchers to develop stimulus-responsive polymeric nanomedicine that achieve burst drug release in response to biological or external triggers. In view of the above, the primary focus of my research is to design, synthesize and characterize multifunctional stimulus-responsive polymer and polymer-hybrid nanovehicles encapsulation of therapeutic agents including anticancer drug and photothermal dye for the triggered drug release and combined photothermal-chemotherapy. In Chapter 2, we aim to prepare multifunctional hollow mesoporous silica nanoparticles (HMSNs) with the polymer coating, which achieved the triggered release of the encapsulated drug molecules under three stimuli independently. By modification of HMSNs with initiating group, pH responsive poly(2-(diethylamino)-ethyl methacrylate) (PDEAEMA) was grafted onto the surface with both reduction cleavable disulfide bond and UV-cleavable o-nitrobenzyl ester linkage. Doxorubicin (DOX) was easily loaded into the polymer-hybrids and quickly released in response to the triggers such as acidic environment, reducing agent or UV irradiation. Despite chemotherapy being the leading therapeutic method for the treatment of cancer, the concept of combination therapy has been further put forward to ensure therapeutic efficacy for cancer. Hence, in chapter 3, we utilized the polymeric DOX prodrug coated HMSNs to load the photothermal dye IR825 for the combined photothermal-chemotherapy. DOX was covalently immobilized on the grafted polymer coating via acid-cleavable hydrazone linkage while released efficiently under weak acidic endo/lysosomal environment. Besides, the hollow space of nanohybrids could also retain NIR absorbing dye IR825 at high loading content for the effective photothermal therapy. In vitro cell studies further demonstrated that the nanohybrids were endocytosed by HeLa cancer cells effectively and anticancer activity was significantly improved by NIR irradiation. Folic acid can bind to numerous types of cancer cells with over-expressed folate receptors and enhance the selectivity and efficiency of drug delivery. In chapter 4, we fabricated the folic acid functionalized polymeric prodrug micelles to load photothermal dye IR825 for the combination therapy. The resulting dye loaded micelles showed excellent colloidal stability and monodispersity in aqueous solutions. Specifically, the conjugated DOX could be efficiently released in response to acidic environment. In addition, the encapsulated dye could convert the NIR irradiation into heat energy with high efficiency, making the self-assembled micelles an effective candidate for photothermal therapy. Significant tumor regression was also observed in the zebrafish liver hyperplasia model after combination therapy. Thus, these as-prepared polymer and polymer-hybrid nanocarriers may provide new insight in cancer treatment with unprecedented therapeutic outcomes.